Industry 4.0 and hyper-customized smart manufacturing supply chains - Ponnambalam, S. G. (Sivalinga Govinda) (Business Science Reference, 2019)
"This book examines all aspects of innovation and operations in smart manufacturing and digital supply chain management in the Industry 4.0 era"--